AI for slogans? A cross-platform, cross-language comparison of AI-generated slogans for sustainable brands - Kovács, László (Linguistik Online, 2026)
Slogans play a central role in branding: they contribute to brand image and are primary touching points between brands and consumers. Slogan generation is not easy because slogans need not only to be in touch with the brand, but they also need to be memorable, catchy, and overall appealing. New technologies, however, such as Generative Pre-trained Transformers (GPT), by different AI platforms, may help in slogan generation. Although AI is researched in many contexts, more research is needed on specific marketing-connected tasks. The current study analyzes and evaluates AI-generated slogans: General and specific slogans connected to sustainable brands are created in English and Hungarian using different AI platforms. The linguistic characteristics of the generated slogans are analyzed, and university students rate Hungarian slogans in five dimensions. Results show that a given software performs differently depending on the criteria used for evaluation, language, the prompt used, and the time of slogan generation; thus, results are hardly generalizable. Due to the results and ethical considerations, AI platforms are recommended for use for brainstorming during slogan generation.